Detention without trial needed in fighting terrorism expert - Borneo Post, (KK) (Borneo Post, 2014)
KUALA LUMPUR: A legal expert says it may be necessary to incorporate detention without trial in the proposed Anti Terrorism Act if the government is really serious about enacting fresh laws to fight terrorism in the country.